2000
DOI: 10.1053/hupa.2000.19433
|View full text |Cite
|
Sign up to set email alerts
|

Glioneuronal tumor with neuropil-like islands

Abstract: Mixed glioneuronal neoplasms are relatively uncommon tumors in the central nervous system. Recently, an unusual glioneuronal tumor arising in adults marked histologically by neuropil-like islands was described. We present a similar case arising in a 23-year-old woman who presented with headaches and seizures and on imaging studies was noted to have a frontal-temporal lobe mass. The patient underwent partial resection of the tumor, which histologically resembled anaplastic astrocytoma, and received a course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…These authors demonstrated p53 immunoexpression in 4/6 cases (66.66%) studied by them and found 1p/19q loss of heterozygosity (LOH) deletion in none. Prayson and Abramovich found up to 40% of the tumor cells to show a positive immunoreactivity for p53 9 . Kevyani et al.…”
Section: Discussionmentioning
confidence: 97%
“…These authors demonstrated p53 immunoexpression in 4/6 cases (66.66%) studied by them and found 1p/19q loss of heterozygosity (LOH) deletion in none. Prayson and Abramovich found up to 40% of the tumor cells to show a positive immunoreactivity for p53 9 . Kevyani et al.…”
Section: Discussionmentioning
confidence: 97%
“…Reported cases were located supratentorially [46], with the exception of one example situated in the cervicothoracic spinal cord [12]. As a rule, the underlying lesions were astrocytomas WHO grade II or III [39, 46]; one case was associated with ependymoma [10]. …”
Section: Glioneuronal Tumour With Neuropil-like Islandsmentioning
confidence: 99%
“…While cases of cerebral GTNI are reported in the literature, 5–8 spinal GTNI are extremely rare and to the best of our knowledge only three case have been described so far 9–11 . We report herein a unique case of pediatric primary spinal cord GTNI with meningeal dissemination.…”
Section: Introductionmentioning
confidence: 83%
“…Rosette‐forming glioneuronal tumors (RGNT) represent a peculiar variant of GNT occurring infratentorially in the fourth ventricle with unusual clinico‐pathological features 2,3 and have been described as an independent entity in the current 2007 World Health Organization (WHO) classification of CNS neoplasms 4 . A distinctive form of glioneuronal tumor with neuropil‐like islands (GTNI) occurring in the cerebrum have been reported in the literature 5,6 . These tumors are composed of small round neurocytic cells immunoreactive to a wide range of neuronal markers, including the neuronal nuclear antigens HuC/D and NeuN, forming large rosette‐like structures around neuropil islands and dispersed in a glial fibrillary background.…”
Section: Introductionmentioning
confidence: 99%